2021
DOI: 10.1007/s00701-021-04922-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of shunt response in the diagnosis and treatment of idiopathic normal pressure hydrocephalus: a systematic review and meta-analysis

Abstract: Background Positive shunt response (SR) remains the gold standard for diagnosing idiopathic normal pressure hydrocephalus (iNPH). However, multiple pathologies mimic iNPH symptoms, making it difficult to select patients who will respond to shunt surgery. Although presenting features, extended lumbar drainage (ELD), infusion test (IT), intracranial pressure monitoring (ICPM), and tap test (TT) have been used to predict SR, uncertainty remains over which diagnostic test to choose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 77 publications
(268 reference statements)
1
32
0
Order By: Relevance
“…However, other studies use the continuous ICP monitoring as a diagnostic tool with similar accuracy [ 23 , 24 ]. A recent systematic review showed that ICPM is statistically the most effective diagnostic test, followed by ELD [ 21 ]. In contrast, Mahr et al showed that a response to ELD yielded the best prediction for the improvement of symptoms following surgery [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies use the continuous ICP monitoring as a diagnostic tool with similar accuracy [ 23 , 24 ]. A recent systematic review showed that ICPM is statistically the most effective diagnostic test, followed by ELD [ 21 ]. In contrast, Mahr et al showed that a response to ELD yielded the best prediction for the improvement of symptoms following surgery [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported different protocols for the diagnosis and management of NPH [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Moreover, different diagnostic tests, such as extended lumbar drainage (ELD), the intracranial pressure monitoring (ICPM), infusion test (IT) and tap test (TT), have been used to predict shunt responders [ 21 , 22 , 23 , 24 ]. However, additional clinical and radiological markers and prospective/randomized studies, along with CSF biomarkers, would improve the diagnostic process, especially the differential diagnosis with other neurodegenerative disorders, and could potentially identify the underpinning mechanisms of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired glymphatic function in AQP4 knockout mice resulted in a 55% reduction in the parenchymal clearance of radio-labeled Aβ ( Iliff et al, 2012 ) due to reduced efflux of ISF to the CSF ( Xu et al, 2015 ). Furthermore, some iNPH patients responding to CSF diversion were presented with persistent disorders of cognitive function and abnormal pulsatile ICP ( Villani et al, 1995 ; Silverberg et al, 2002 ; Zhang et al, 2020 ; Kundishora et al, 2021 ; Thavarajasingam et al, 2021 ), indicating impaired intracranial compliance and underlying pathological changes. A main histopathological finding was astrogliosis and reduction of AQP4 and of Dp71 in astrocytic perivascular end-feet.…”
Section: Human Genetic Studies Of Hydrocephalusmentioning
confidence: 99%
“…Although the causes of obstructive hydrocephalus are not difficult to explore, the etiological factors of congenital and/or communicating hydrocephalus remain unclear. Moreover, up to 78% of hydrocephalus patients treated with functional shunting continue to suffer from cognitive function disorders, such as intellectual disability, memory loss, learning disabilities, and spasticity, suggesting that the etiology of hydrocephalus may be related to multiple factors ( Villani et al, 1995 ; Silverberg et al, 2002 ; Zhang et al, 2020 ; Kundishora et al, 2021 ; Thavarajasingam et al, 2021 ). Accumulating evidence suggests that many molecular changes are involved in the pathogenesis of hydrocephalus, and about 40% of hydrocephalus may have a possible genetic etiology ( Haverkamp et al, 1999 ; Zhang et al, 2006 ; Kundishora et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the fulfillment of the clinical and imaging criteria of “probable” or “possible” iNPH does not predict clinical response to shunt surgery ( 2 , 4 ). To predict whether a symptomatic patient suffers “shunt-responsive iNPH”, supplemental tests have included the assessment of clinical response to CSF drainage of short (Tap test) or long (extended lumbar drain) duration, measurements of the CSF pressure change following fluid infusion to the lumbar or ventricular CSF space (infusion tests) or long-term monitoring of static/pulsatile intracranial pressure (ICP) ( 4 8 ). Proper patient selection is worthwhile since shunt surgery may be accompanied by lasting symptom improvement in a substantial proportion of patients ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%